2013
DOI: 10.1097/nmd.0b013e318288e26a
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Relation Between Spirituality and Well-Being

Abstract: Koenig (J Nerv Ment Dis 196:349-355, 2008) and others have asserted that measures of spirituality used to investigate its association with health seem to present a misleading picture of the relationship because of evidence suggesting that spirituality has become conceptually confounded with well-being. To evaluate this claim, the present study used a sample of 247 university students to explore the relation of a multidimensional model of spirituality with several different forms of well-being and the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 48 publications
3
24
0
2
Order By: Relevance
“…Correlations between the ESI-R dimensions and the SPWB are very similar to what has been found in other studies (e.g., Migdal & MacDonald, 2013), with EWB obtaining significant moderate-to-strong correlations with all six SPWB subscales. Outside of this, COS was found to correlate significantly with SPWB Self-Acceptance (r = .15, p <.01), Personal Growth (r = .25, p <.001), and Purpose in Life (r = .14, p <.01).…”
Section: Confirmatory Factor Analysis (Cfa)supporting
confidence: 76%
See 2 more Smart Citations
“…Correlations between the ESI-R dimensions and the SPWB are very similar to what has been found in other studies (e.g., Migdal & MacDonald, 2013), with EWB obtaining significant moderate-to-strong correlations with all six SPWB subscales. Outside of this, COS was found to correlate significantly with SPWB Self-Acceptance (r = .15, p <.01), Personal Growth (r = .25, p <.001), and Purpose in Life (r = .14, p <.01).…”
Section: Confirmatory Factor Analysis (Cfa)supporting
confidence: 76%
“…Since the instrument has been found to have good psychometric properties with other cultural samples, we expected the ESI-R to show the same with a Spanish sample. Second, we were interested in seeing if we could replicate published empirical findings with the ESI-R with regard to its associations to age, sex, personality, well-being, and psychopathology (MacDonald, 2000a;MacDonald et al, 2015;MacDonald & Holland, 2003;Mendez & MacDonald, 2012;Migdal & MacDonald, 2013). The available research generally indicates that one or more of MacDonald's (2000aMacDonald's ( , 2000b dimensions (a) show modest but positive associations with age, (b) are linked with sex such that women tend to get higher scores (especially on REL, followed by COS and PAR), (c) are related to personality traits in the well-known MacDonald's (2000a) five dimensional model of spirituality.…”
Section: International Journal Of Transpersonal Studies 111mentioning
confidence: 99%
See 1 more Smart Citation
“…There are other reasons, however, why EWB was a candidate for exclusion. These reasons include (a) MacDonald (2000b) did not find a higher order EWB factor in his original study, (b) there have been questions raised regarding the appropriateness of incorporating any well-being concepts within measures of spirituality (including the ESI-R) as it results in a confounding of the two constructs which undermines the usability of spirituality measures in health research (Koenig, 2008;Migdal & MacDonald, 2013), and (c) other than one PAR item, the EWB items are the only ones on the ESI-R which are reverse scored and use more negative phrasing. Not only is it more challenging to effectively translate negatively worded items from one language to another, research has suggested that the inclusion of such items on a test which otherwise uses positively phrased items runs the risk compromising the quality of measurement (e.g., Roszkowski & Soven, 2010).…”
Section: International Journal Of Transpersonal Studies 129 Expressiomentioning
confidence: 99%
“…They state in their Introduction that ''R/S wellness is of increasing interest in the medical literature and may protect against depressive symptoms'', which suggests causality. We do not understand why the authors used the concept of spiritual wellbeing (SWB) to predict wellbeing, given the warnings against this practice in several earlier publications (Koenig, 2008;Visser et al, 2010;Migdal & MacDonald, 2013).…”
mentioning
confidence: 99%